2015
DOI: 10.1039/c5ra00871a
|View full text |Cite
|
Sign up to set email alerts
|

Wearable temperature sensor based on graphene nanowalls

Abstract: This work reports an ultrasensitive wearable temperature sensor based on GNWs/PDMS for personalized healthcare and human–machine interface systems.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
244
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 280 publications
(247 citation statements)
references
References 35 publications
3
244
0
Order By: Relevance
“…Graphene nanowalls, made of vertically aligned interlaced graphene nanosheets, were transferred onto a PDMS substrate to fabricate flexible temperature sensors (Figure 2a). [78] With the thermal expansion of the PDMS substrate at elevated temperature, the interlaced graphene nanowall network became more loosely connected, resulting in an increase in resistance. In a NTC type temperature sensor based on graphene sensing elements and AgNW electrodes (Figure 2b,c), the temperature sensitivity can be tuned by strain.…”
Section: Wearable Temperature Sensorsmentioning
confidence: 99%
See 2 more Smart Citations
“…Graphene nanowalls, made of vertically aligned interlaced graphene nanosheets, were transferred onto a PDMS substrate to fabricate flexible temperature sensors (Figure 2a). [78] With the thermal expansion of the PDMS substrate at elevated temperature, the interlaced graphene nanowall network became more loosely connected, resulting in an increase in resistance. In a NTC type temperature sensor based on graphene sensing elements and AgNW electrodes (Figure 2b,c), the temperature sensitivity can be tuned by strain.…”
Section: Wearable Temperature Sensorsmentioning
confidence: 99%
“…Reproduced with permission. [78] Copyright 2015, Royal Society of Chemistry. b) Schematic diagram of the stretchable graphene thermistor consisting of graphene thermoresistive sensing element and AgNW electrodes.…”
Section: Wearable Temperature Sensorsmentioning
confidence: 99%
See 1 more Smart Citation
“…These sensors generally have a high resolution of temperature, but the complicated structural design and sophisticated fabrication process may hinder their further applications. Active materials with negative temperature coefficients, such as metal oxides [145,146], CNTs [127,147,148], graphene (including rGO) [81,94,149,150], which show decreased resistance with increased temperature, have also been extensively investigated for the fabrication of flexible temperature sensors. The temperature sensors based on these active materials, especially carbon materials, generally have simple fabrication processes and excellent properties, benefiting their applications as wearable sensors for human health monitoring.…”
Section: Flexible Temperature Sensorsmentioning
confidence: 99%
“…Actually, GNWs have been proven to possess excellent light absorption from NIR to MIR region [23][24][25] due to the abundance of edges and index of refraction close to unity at the interface. Additionally, our previous work [26] reported that GNWs have a considerably high TCR. Furthermore, in terms of IR detectors, GNWs also show a great market potential.…”
Section: Introductionmentioning
confidence: 99%